2015
DOI: 10.2138/am-2015-5190
|View full text |Cite
|
Sign up to set email alerts
|

Composition dependence of spin transition in (Mg,Fe)SiO3bridgmanite

Abstract: Spin transitions in (Mg,Fe)SiO 3 bridgmanite have important implications for the chemistry and dynamics of Earth's lower mantle, but have been complex to characterize in experiments. We examine the spin state of Fe in highly Fe-enriched bridgmanite synthesized from enstatites with measured compositions (Mg 0.61 Fe 0.38 Ca 0.01 )SiO 3 and (Mg 0.25 Fe 0.74 Ca 0.01 )SiO 3 . Bridgmanite was synthesized at 78-88 GPa and 1800-2400 K and X-ray emission spectra were measured on decompression to 1 bar (both composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 75 publications
4
10
0
Order By: Relevance
“…Pressure-induced spin transitions have now been identified in multiple minerals that may be present in the lower mantle [Badro, 2014;Lin et al, 2013]. However, the mechanism, pressure, and compositional dependence of the spin state of bridgmanite (Bdgm), the most abundant lower mantle phase, remains controversial [Badro et al, 2004;Catalli et al, 2010Catalli et al, , 2011Dorfman et al, 2015;Kupenko et al, 2015;Li et al, 2004;Lin et al, 2012;McCammon et al, 2010;Mohn and Trønnes, 2016;Zhang and Oganov, 2006]. The main reason for this controversy arises from its crystal chemical complexity, in which the iron can be distributed between two nonequivalent crystallographic positions: large pseudododecahedral (A) sites and relatively small octahedral (B) sites [McCammon, 1997].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Pressure-induced spin transitions have now been identified in multiple minerals that may be present in the lower mantle [Badro, 2014;Lin et al, 2013]. However, the mechanism, pressure, and compositional dependence of the spin state of bridgmanite (Bdgm), the most abundant lower mantle phase, remains controversial [Badro et al, 2004;Catalli et al, 2010Catalli et al, , 2011Dorfman et al, 2015;Kupenko et al, 2015;Li et al, 2004;Lin et al, 2012;McCammon et al, 2010;Mohn and Trønnes, 2016;Zhang and Oganov, 2006]. The main reason for this controversy arises from its crystal chemical complexity, in which the iron can be distributed between two nonequivalent crystallographic positions: large pseudododecahedral (A) sites and relatively small octahedral (B) sites [McCammon, 1997].…”
Section: Main Textmentioning
confidence: 99%
“…Mőssbauer spectroscopy (traditional or synchrotron) can be used to infer the iron oxidation/spin states as well as the site occupancies, but the relation of hyperfine parameters to various iron states is not straightforward, and as a result, the interpretation of Mőssbauer spectra is generally inconclusive [Dyar et al, 2006]. Combined XES and Mössbauer studies helped to partially resolve the problem [Catalli et al, 2010[Catalli et al, , 2011Dorfman et al, 2015;Lin et al, 2016] but are still inefficient in probing a broad range of chemical compositions because they require extraordinary access to synchrotron X-ray sources.…”
Section: Main Textmentioning
confidence: 99%
“…Solid black lines are modeled velocity profiles of Run 2 using thermoelastic equations. In contrast, both Fe 3+ and Fe 2+ in the A site have been reported to remain in the HS state throughout the entire lower-mantle pressure range (24-130 GPa) (Dorfman et al, 2015;Hsu et al, 2010Hsu et al, , 2011Lin et al, 2016). In contrast, both Fe 3+ and Fe 2+ in the A site have been reported to remain in the HS state throughout the entire lower-mantle pressure range (24-130 GPa) (Dorfman et al, 2015;Hsu et al, 2010Hsu et al, , 2011Lin et al, 2016).…”
Section: Resultsmentioning
confidence: 91%
“…Earlier studies have indicated that drastic softening of K S and V P could occur across the spin transition of Fe in lower-mantle Fe-bearing minerals, such as ferropericlase, magnesiosiderite, and the new hexagonal aluminous phase Lin et al, 2013;Wu et al, 2013Wu et al, , 2016Yang et al, 2015). Similarly, but distinct from the aforementioned Fe-bearing minerals, the spin and valence transitions of Fe in bridgmanite have been much debated due to its complicated crystal chemistry as well as the coupled substitution possibility of Al and Fe in crystallographic sites of bridgmanite (Catalli et al, 2010(Catalli et al, , 2011Dorfman et al, 2015;Hsu et al, 2011;Lin et al, 2016;Mao et al, 2015). The current consensus is that both ferrous (Fe 2+ ) and ferric (Fe 3+ ) iron can be incorporated into bridgmanite, where Fe 3+ can occupy both the large dodecahedral site (A site) and octahedral site (B site), while Fe 2+ only occupies the A site Mao et al, 2015;Shukla et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation